Silent Treatment Terhadap Mahasiswa Akhir: Tinjauan Sosiologis - Aura Yuwanda; Masitah Sri Rayawati; Sarah Aulia Nanda; Ade Mere Dewa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Silent treatment as a form of passive-aggressive communication triggers negative impacts on social relationships and individual psychological well-being. The study aims to understand the meaning of silent treatment from supervisors to final students and analyze the social impact that occurs in the final student environment, such as explaining the impact of silent treatment on students social condit, namely stress and social exclusion. This research uses a qualitative method based on the theory of symbolic interactionism, where the theory emphasizes social meaning can be formed through interactions and also individual interpretations of symbols, language actions including silence or silent treatment, in this study we used five informants of final students of Sociology at Riau University. It can be concluded that social education and counseling services ae needed to prevent silent treatment among final year students.